Identification of hemolytic anemia in Korean indigenous cattle with a criteria value of reticulocyte count, indirect bilirubin, and L-lactate concentration - Jung, Youngwoo; Ku, Ji-Yeong; Kim, Youngjun; Kim, WooChan; So, Hyungjae; Piao, Lianfu; Yoon, Ji-Seon; Park, Jinho (Frontiers in Veterinary Science, 2024)
Bovine hemolytic anemia has a negative impact on animal welfare and productivity due to its associated clinical symptoms. Hemolysis is generally known to cause reticulocytosis, increased indirect bilirubin, decreased concentration of haptoglobin, and increased lactate dehydrogenase. Additionally, tissue hypoperfusion due to concomitant anemia increases blood lactate concentration. However, few studies have reported the correlation between these indicators and hemolytic anemia in cattle. We expected that alterations in hematological and biochemical parameters could identify cattle with hemolytic anemia. Therefore, in addition to reporting differences in indicators according to hemolytic anemia, this study aimed to derive indicators and set criteria for identification of bovine hemolytic anemia. In cattle with hemolytic anemia, reticulocytosis, increased indirect bilirubin, and increased L-lactate were observed, and the correlation of these indicators with hematocrit (HCT) was confirmed. And since HCT alone has limitations in identifying hemolytic anemia, we suggest additional criteria to identify hemolytic anemia in cattle.